Compilation of the structural model of emotional divorce based on the dark triple traits of personality and conflict resolution styles - Sadeghkhani, Marjan; Emamipour, Susan; Mirhashemi, Malek (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: The present research was conducted in order to model structural equations of emotional divorce based on dark personality traits and conflict resolution styles. Methods and Materials: The study used descriptive-correlational method based on structural equations. The statistical population of this research consisted of all married women in the age group of 25-50 years of Tehran Azad University, Yadgar Imam (RA), Abol Fattouh Razi and North Tehran units in the first half of 2021, which was available online through the sampling method. (due to the spread of the corona virus) were chosen. The research tools were Gottman’s (1995) emotional divorce questionnaire, Johnson and Webster’s (2010) dark personality triangle, and Rahim’s (1983) conflict resolution styles. Analyzes were done using SPSS and AMOS software. Findings: The results showed that there is a significant negative and positive relationship between constructive conflict resolution style (β=0.188) and non-constructive conflict resolution style (β=0.170) with emotional divorce, respectively (p<0.01). A significant positive relationship is observed between Machiavellianism trait and emotional divorce (β=0.173). Also, a significant positive relationship was found between antisocial trait (β=-0.140) and narcissism (β=-0.153) with emotional divorce (p<0.01). Conclusion: Dark traits and constructive conflict resolution styles can predict emotional divorce in addition to having a direct effect on emotional divorce